2016
DOI: 10.4314/sajas.v45i5.5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of bovine GHR, IGF-1 and IGFBP-3 genes in Indian cattle and buffalo

Abstract: The identification of genetic polymorphisms in the genes that play a crucial role in regulatiing growth and development of livestock enables us to evaluate the biological similarities and to acquire a better perspective of quantitative traits. The present study was undertaken to characterize genetic variability in the bovine growth hormone receptor (GHR), insulin-like growth factor 1 (IGF-1) and insulin-like growth factor binding protein 3 (IGFBP-3) genes among Bos indicus (Malnad Gidda, Khillar), Bos taurus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
(32 reference statements)
1
12
0
1
Order By: Relevance
“…GH is an anabolic hormone synthesized and secreted by the somatotroph cells, it is a major regulator of postnatal growth and metabolism in mammals, and it plays an important role in lactation, protein, lipid and carbohydrate metabolism, tissue growth, and fertility in cows (Akers, 2006;Lucy, 2008;Thidar et al, 2008). The growth promoting and metabolic actions of GH are generally mediated by the insulin-like growth factor I (IGF-I) (Ramesha et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…GH is an anabolic hormone synthesized and secreted by the somatotroph cells, it is a major regulator of postnatal growth and metabolism in mammals, and it plays an important role in lactation, protein, lipid and carbohydrate metabolism, tissue growth, and fertility in cows (Akers, 2006;Lucy, 2008;Thidar et al, 2008). The growth promoting and metabolic actions of GH are generally mediated by the insulin-like growth factor I (IGF-I) (Ramesha et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to Othman et al (2014), IGFBP-3 can be used as a marker for the function of growth, metabolism, reproduction, immunity and energy balance in cattle. SNP is a condition where the presence of a different nucleotide constituent of a gene, and studies of SNP on IGFBP-3 gene in sheep, goat, cattle and buffalo have been reported (Rodríguez et al 2013;Mahrous et al 2014;Ramesha et al 2015;Rasouli et al 2016). SNP in the IGFBP-3 gene was reported in Egypt cattle (Othman et al 2014), Holstein and Cross between Holstein-Haryana (Choudhary et al 2007), Hanwoo (Kim et al 2005) and various Chinese cattle (Gao et al 2009;Liu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…GH and GHR were previously reported as particular gene regions for meat yield in farm animals, and they were selected as candidate genes for molecular selection (Biswas et al, 2003;Andreas et al, 2010). Specific primer pairs that were previously described for cattle (Maciulla et al, 1997) were used for these two gene regions in water buffaloes, and PCR products were obtained with similar fragment lengths from water buffalo samples (Andreas et al, 2010;Ramesha et al, 2015).…”
Section: Discussionmentioning
confidence: 99%